An improvement of competitive exercises performing on the rings by 10–12 year old gymnasts using special physical training - Дейнеко, Альфія (Slobozhanskyi Herald of Science and Sport, 2017)
Alfiya Deyneko Purpose: to reveal the influence of the level of special physical readiness of gymnasts of 10–12 years on the technique of performing exercises on rings. Material & Methods: for the task of testing the level of special physical and technical preparedness were carried out gymnasts of 10–12 years, who are trained on the basis of Sports School of high sportsmanship Kharkov. Result: based on the results of the study, the dynamics of qualitative and quantitative indicators of the level of special physical preparedness of gymnasts aged 10–12 years and its influence on the technique of performing a competition program on rings. Conclusion: results of the experiment confirm the effectiveness and significance of the use of special physical training that positively influence the technique of performing a competitive combination on the gymnasts' rings during the preliminary basic training.